KECANDUAN GADGET DAN PERKEMBANGAN EMOSI SISWA SMP MUHAMMADIYAH 1 PEKANBARU - Ainurrahmah Ainurrahmah; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: ComRes conducted a polling study for Channel 4 News television channel. The survey results show about 47% of parents say that their children spend a lot of time in front of the gadget. While the other 43% confess their children have an emotional bond with gadget devices owned. Excessive used of gadgets can cause social inequalities in their society. If it glued to the sophistication of gadgets, then students will find it difficult in expressing emotions that exist in their difficulty to communicate with their environment. Students are more pleased and concerned with the gadget than their environment. Therefore, researchers feel the need to analyze the gadget addiction and emotional development of these students. The purpose of this researches are: To determine the behavior and to know the emotional development of students are addicted to gadgets. The sample in this research were 34 students. This research uses descriptive method with quantitative approach. Data collection techniques used questionnaires. To analyze data using percentage technique. The results of this study are: Addiction of gadgets to the students of SMP Muhammadiyah 1 Pekanbaru generally seen from the level of addiction is in the mild category, which their use gadgets for a long time but controlled. Judgment from the dominant addiction indicator is in the high category, their feeling of displeasure, the appearance of irritability when their use of gadgets is limited, and tend to repeat their behavior of playing gadgets. The student's emotional development is largely in the good category. They are able to develop and control the emotions that exist in him. Suggestions of this research are: direct and supervise students in using gadgets, and pay attention to the child's emotional development in order to achieve optimally.Key Words: Addiction, Gadget, Emotion